Information security science : measuring the vulnerability to data compromises - Young, Carl S. (Cambridge, MA : Syngress is an imprint of Elsevier, 2016)
Provides the scientific background, analytic methods, and quantitative metrics to allow scientists and engineers with no background in security to estimate vulnerability to a spectrum of information security threats. Explores the physical nature of information security risk, and in so doing exposes connections between information security, physical security, information technology, and information theory.
I. Threats, risk and risk assessments -- Information security threats and risk -- Modeling information security risk -- II. Scientific fundamentals -- Physics and information security -- Electromagnetic waves -- III. The compromise of signals -- Signals of information security -- The compromise of electromagnetic signals -- Countermeasures to electromagnetic signal compromises -- Visual information security -- Audible information security -- IV. Information technology risk -- Information technology risk factors -- Information technology risk measurements and metrics -- Special information technology risk measurements and metrics -- V. The physical security of information assets -- Physical security controls -- Data centers : a concentration of information security risk.
Includes index.
Online resource; title from PDF title page (ScienceDirect, viewed July 11, 2016).
Includes bibliographical references and index.
Keywords: Computer security; Information technology -- Security measures; Computer security; Information technology -- Security measures; Electronic books